'Time‐free' preventive maintenance of systems with structures described by signatures. (2nd February 2015) - Finkelstein, Maxim; Gertsbakh, Ilya
Abstract : A new approach to optimal maintenance of multicomponent systems (networks) is suggested. It is applied to systems subject to external shock processes. Signatures are used for description of systems structures and for dealing with the corresponding optimal maintenance problems. The number of shocks experienced by a system defines a discrete parameter for minimization of the long‐run costs per unit of time and is viewed as an alternative scale. The optimal preventive maintenance is performed either after the shock with the obtained optimal number or the corrective maintenance (replacement) of the whole failed system occurs, whichever comes first. A numerical example is considered and the comparison with the age‐based preventive maintenance is performed. Copyright © 2015 John Wiley & Sons, Ltd.